Delta Opioid Receptor Signaling Promotes Resilience to Stress Under the Repeated Social Defeat Paradigm in Mice - Henry, Mathilde S.; Bisht, Kanchan; Vernoux, Nathalie; Gendron, Louis; Torres-Berrio, Angélica; Drolet, Guy; Tremblay, Marie-Ève (Frontiers in Molecular Neuroscience, 2018)
The adaptation to chronic stress is highly variable across individuals. Resilience to stress is a complex process recruiting various brain regions and neurotransmitter systems. The aim of this study was to investigate the involvement of endogenous opioid enkephalin (ENK) signaling in the development of stress resilience in mice. The translational model of repeated social defeat stress was selected to mimic the unpredictable disruptions of daily life and induce resilience or vulnerability to stress.  As in humans, adult C57BL/6J mice demonstrated a great variability in their response to stress under this paradigm. A social interaction test was used to discriminate between the phenotypes of resilience or vulnerability to stress. After social defeat, the expression levels of ENK mRNA and their delta opioid receptors (DOPr) were quantified in the basolateral amygdala (BLA) and BLA-target areas by in situ hybridization. In this manner, ENK mRNA levels were found to decrease in the BLA and those of DOPr in the ventral hippocampus CA1 of vulnerable mice only. Stimulating the DOPr pathway during social defeat by pharmacological treatment with the nonpeptide, selective DOPr agonist SNC80 further induced a resilient phenotype in a majority of stressed animals, with the proportion of resilient ones increasing from 33% to 58% of the total population. Ultrastructural analyses additionally revealed a reduction of oxidative stress markers in the pyramidal cells and interneurons of the ventral hippocampus CA1 upon SNC80 treatment, thus proposing a mechanism by which ENK-DOPr signaling may prevent the deleterious effects of chronic social stress.